Modelling of a Parabolic Trough Collector System for Hot Water Production - Kalogirou, Soteris A.; Lloyd, Stephen J.; Ward, John Paul (My University, 1993)
The modelling of a Parabolic Trough Collector System for the hot water production is presented. This is followed by an experimental verification of the model and analysis of the experimental results. The difference between the predicted and actual results is about 7%. This variation is attributed to the difference of the actual weather during the tests compared to standard data taken from a "reference yea" and the convection losses from the collector receiver which were not constant as accounted by the program.
Keywords: Parabolic Trough Collector System